Electric field-driven one-step formation of vertical p–n junction TiO2 nanotubes exhibiting strong photocatalytic hydrogen production. Issue 4 (6th January 2021) - Kim, Moonsu; Lee, Jaewon; Je, Minyeong; Heo, Bumgi; Yoo, Hyeonseok; Choi, Heechae; Choi, Jinsub; Lee, Kiyoung
Abstract : The electrochemically prepared anodic p–n junction TiO2 nanotubes leads to enhancing visible light absorption and high photocatalytic H2 production. Abstract : In this study, vertically aligned p–n junction TiO2 nanotubes can be formed by anodization of the Ti substrate following the addition of a high electric field in a Pd precursor-containing electrolyte. The bottom region of the TiO2 nanotubes with a high concentration of Pd because of the high electric field which was induced to be p-type. In contrast, the region with a low Pd concentration (top of the TiO2 nanotubes) was determined to be n-type, similar to the pristine TiO2 . The concentration profile of the dopant in TiO2 nanotubes was investigated via TOF-SIMS and XPS. Defect formation energies in TiO2 nanotubes were estimated using density-functional theory calculation to understand the p–n junction formation. The p–n junction TiO2 nanotubes showed a high photocatalytic hydrogen production rate of 25.2 μL cm −2 h −1 under solar light irradiation as a result of the enhancement of visible light photoactivity.